The Influence of Leadership, Social Competence, and Work Motivation on Employee Performance at Perumda Pasar Argha Nayottama, Buleleng Regency - Ketut Krisna Prasetya; Kadek Rai Suwena; Trianasari Trianasari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Employee performance is a key factor in achieving organizational goals, especially in the public service sector such as Perumda Pasar Argha Nayottama, Buleleng Regency. Low work effectiveness is often influenced by internal and external factors of employees, including leadership style, social competence, and work motivation. This study aims to determine the effect of leadership, social competence, and work motivation on employee performance, both partially and simultaneously. The method used is a quantitative approach with multiple linear regression analysis techniques. Data were collected through questionnaires distributed to the entire employee population at Perumda Pasar Argha Nayottama. The results of the study indicate that the three independent variables have a positive and significant effect on employee performance. Inspirational and supportive leadership encourages motivation and strengthens social competence. Social competence contributes to the creation of healthy collaboration in the work environment, while work motivation has been proven to be the main driver in increasing employee productivity. Simultaneously, these three variables support each other in forming optimal employee performance. These findings provide practical implications for management to develop an integrated and humanistic human resource approach in improving the quality of public services.